2017
DOI: 10.1128/msphere.00251-17
|View full text |Cite
|
Sign up to set email alerts
|

Collection of Viable Aerosolized Influenza Virus and Other Respiratory Viruses in a Student Health Care Center through Water-Based Condensation Growth

Abstract: The significance of virus aerosols in the natural transmission of respiratory diseases has been a contentious issue, primarily because it is difficult to collect or sample virus aerosols using currently available air sampling devices. We tested a new air sampler based on water vapor condensation for efficient sampling of viable airborne respiratory viruses in a student health care center as a model of a real world environment. The new sampler outperformed the industry standard device (the SKC BioSampler) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 30 publications
(42 reference statements)
1
42
0
Order By: Relevance
“…For laboratory-generated infectious IAV, the GTC's collection efficiency was seven times higher than that of the BioSampler . For realworld sampling, the GTC collected more types of airborne viruses and higher quantities per sampling run than the BioSampler (Pan et al 2017). These results indicate the GTC can be used for surveillance of airborne viruses.…”
Section: Water-based Condensationmentioning
confidence: 92%
See 1 more Smart Citation
“…For laboratory-generated infectious IAV, the GTC's collection efficiency was seven times higher than that of the BioSampler . For realworld sampling, the GTC collected more types of airborne viruses and higher quantities per sampling run than the BioSampler (Pan et al 2017). These results indicate the GTC can be used for surveillance of airborne viruses.…”
Section: Water-based Condensationmentioning
confidence: 92%
“…Although droplet infection is the commonly described mode of transmission for influenza viruses, they have also been detected in aerosols 'far away' (>1 m) from infected patients in a few studies. For example, influenza A H1N1 and H3N2, and B viruses, were collected by a water-based sampler located >2 m from patients in a student infirmary (Pan et al 2017), and airborne influenza A H3N2 was collected by a Sioutas impactor 3Á7 m away from sick individuals (Lednicky and Loeb 2013).…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.1371/journal.ppat.1008362.g001 the tunnel opening), with a decline in plaque count seen by plate 2 (at 60cm) and plate 3 (at 90cm) Following 10-minutes exposure of cell culture plates to nebulised particles, we sampled any non-sedimenting aerosols from the air within the IVTT into an SKC Biosampler. The SKC Biosampler, which can collect particles with aerodynamic diameter of 0.3μm to 8μm [17,18], is a device that has been previously used for collection of viable airborne influenza viruses and cited to be one of the more efficient available methods [19], being used as a standard with which to compare other techniques [20][21][22]. No infectious virus was collected from the air sample, whereas tracer DNA and viral RNA were detected (S1 Fig).…”
Section: Establishing a System To Collect Infectious Influenza Virus mentioning
confidence: 99%
“…Previous studies have reported detection of influenza and other respiratory virus-laden particles in the exhaled breath of symptomatic patients [12][13][14][15] or in air sampled at healthcare facilities [16][17][18][19]. It is currently unknown if people with mild or subclinical respiratory infections, who are capable to continue their daily activities in the community without substantial impediment, may also release virus-laden particles with airborne transmission potential.…”
mentioning
confidence: 99%